Rattus leucopus - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Rattus leucopus (Gray, 1867). Proc. Zool. Soc. Lond., 1867:598. TYPE LOCALITY: Australia, Queensland, Cape York = Locality of lectotype (see Mahoney and Richardson, 1988:183). DISTRIBUTION: Australia, Queensland; one population ranges from the tip of Cape York south down the E side of the Peninsula to the vicinity of Coen, another from the region of Cooktown south along the coast to Tully; all records are east of the Great Dividing Range (see maps in Taylor and Horner, 1973:43; Watts and Aslin, 1981). New Guinea; widespread in lowlands south of Central Cordillera, and in N and S lowland regions fringing the Owen Stanley Range (see map in Taylor et al., 1982:232). SYNONYMS: cooktownensis, dobodurae, mcilwraithi, personata, ratticolor, ringens, terra-reginae. COMMENTS: This species and R. sordidus are the only two native Rattus occurring on both New Guinea and the NE coastal region of Australia (Taylor et al., 1982). Morphologically related to other species of Rattus native to New Guinea (Taylor et al., 1982). Morphological data interpreted by Taylor and Horner (1973) to indicate close affiliation between R. leucopus and R. fuscipes from coastal Queensland; genic data discordant with this view (Baverstock et al., 1983a, 1986). Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 654, DOI: 10.5281/zenodo.7353098